Poéticas ludonarrativas: a atividade ergódica e a experiência estética em jogos eletrônicos - Silva, Allan Defensor (2021)
The present dissertation inserts the study of games, under theoretical approach by Johan Huizinga and Roger Caillois, into Espen Aarseth’s ergodic literature paradigm, and dialogues towards the perspective that, in some computer games, an unending bond can be seen between play and literary procedures. From the verification of commonly narrative-related mimetic elements, it starts to understand such works as ludonarratives, which possess an intersemiotic relationship between their ludic and narrative procedures. However, by the manipulation of such works by a cyber-reader, whose concept is a potence of that who, according to Santaella, is the immersive reader, ludonarrative poetics emerge from this semiosis yet to be observed. In addition to revisiting Peircean Semiotics interpretative concepts (Santaella, Zilocchi) and from theoretical movements that seek to relate technology imbued artistic manifestations such as cyberception (Arantes, Domingues, Santaella) and game studies (Aarseth, Ryan), it takes as a main reference the work Braid (Blow, 2008) and investigates the procedure by which the cyber-reader subscribes her experience into the work’s cybertext, in an effort that is not solely interpretative, but also of ludic manipulation of its temporal and spatial elements, the ergodic activity. In tune with theoretical references according to Arantes, Domingues and Gomes, we signify the cyber-reader as an interfaced subject who goes inside narrative detail and reorganizes its values according to electronically disposed interventive permissions